The Neuroprotective Effect of Ursodeoxycholic-acid in Comparison with Carbamazepine in Pilocarpine Induced Status Epilepticus in Experimental Rats - Omran, Zainab Adel; Jwied, Ahmed Hamed (AL-Kindy College Medical Journal, 2025)
Background: An epileptic seizure was defined as a transient occurrence of signs and symptoms due to abnormal excessive neuronal activity in the brain. A seizure lasting 30 minutes or longer or a series of seizures in which the patient did not regain normal mental status between convulsions was considered a status epilepticus. Pilocarpine is a drug that acts as an acetylcholine muscarinic agonist. Carbamazepine is a psychotropic medication that is frequently provided to patients with psychological illnesses and epilepsy conditions often treated with anticonvulsant medication carbamazepine. Ursodeoxycholic acid, Ursodiol also known as secondary bile acid, is produced by gut bacteria in most other species including humans. The aim of this study was conducted to evaluate the possible neuroprotective effects of Ursodeoxycholic-acid in comparison to carbamazepine against pilocarpine-induced status epilepticus in experimental rats.Subjects and Methods: Thirty male Wistar albino rats were utilized in this study, Group I (Control group): Rats received normal saline orally for 3 days. Group II (Lithium chloride + Scopolamine + Pilocarpine): Rats were given lithium chloride followed by pilocarpine administration; scopolamine is also given to the rats 30 minutes before pilocarpine administration. Group III (Carbamazepine): status epilepticus rats received carbamazepine orally for 3 days. Group IV (Small dose of Ursodeoxycholic-acid): status epilepticus rats received Ursodeoxycholic-acid 25 mg/kg/day orally for 3 days. Group V (Large dose of Ursodeoxycholic-acid): pilocarpine-treated rats received UDCA 100 mg/kg/day orally for 3 days.Results: Based on the measurement of markers: Caspase3, Tumor Necrosis Factor-alpha, and Reduced Glutathione we reported rise in the serum level of Reduced Glutathione, and decrease in the serum level of Caspase3, and Tumor Necrosis Factor-alpha in Ursodeoxycholic-acid treated-group.Conclusions: It can be concluded that the Ursodeoxycholic-acid has a neuroprotective effect to epileptic rats recognized by its anti-apoptotic, anti-inflammatory, and antioxidant effects